RELATIONSHIP BETWEEN PATIENT FACTORS AND PSYCHOLOGICAL WELL-BEING IN TYPE 2 DIABETES MELLITUS PATIENTS - Umam, Khotibul; Iswatun, Iswatun; Susanto, Joko; Sri Wijayanti, Endah; Paramadita, Yayuk (Universitas Airlangga, 2024)
Introduction: Psychological well-being is an individual's feelings about everything from trauma to acceptance of life. Diabetes mellitus is a chronic disease that is a major problem in the world of health and a disease that has the most consequences on physical, psychological, and social. Every type 2 diabetes mellitus patient has a different psychological condition, some have high psychological well-being and some have low psychological well-being. This study aimed to analyze the relationship between patient factors and psychological well-being in type 2 diabetes mellitus patients at the Tikung Lamongan Health Center UPT. Methods: This research method is quantitative with a correlational research design. The sampling technique used consecutive sampling, samples were taken on March 24 - April 2, 2022 at the Tikung Lamongan Health Center UPT with a total of 57 respondents. The instruments used were the SPWB Ryff questionnaire (1995), demographic data, and religiosity questionnaire compiled by Kartika (2017), while the data analysis used the chi-square test from SPSS. Results: The results showed no relationship between patient factors based on age, gender, education, and psychological well-being in patients with type 2 diabetes mellitus because it had an Asymp. Sig. (2-sided) value > 0.05, while patient factors based on religiosity were related to psychological well-being because it had an Asymp. Sig. (2-sided) value of 0.000. Conclusions: This study is expected to increase information and knowledge about efforts to prevent and control type 2 diabetes mellitus so that the psychological well-being that is owned increases.